The Kremlin's candidate : a novel - Matthews, Jason, 1951-2021- (Scribner, 2018)
Russian counterintelligence chief Colonel Dominika Egorova has been a recruited asset of the CIA, stealing Kremlin secrets for her CIA handler Nate Nash for over seven years. In the dazzling finale to the Red Sparrow Trilogy, their forbidden and tumultuous love affair continues, mortally dangerous for them both, but irresistible. In Washington, a newly-installed US administration is selecting its Cabinet members. Dominika hears a whisper of a closely-held Kremlin operation to place a mole inside a high intelligence position. But it's worse than that: One of the three candidates under consideration has been a paid Russian spy for a decade, selling precious US secrets. If the Kremlin's candidate for the position is confirmed, the Russians will have access to all the names of assets spying for CIA in Moscow, including Dominika's. But which of the three individuals is the mole? Dominika's report triggers a desperate mole hunt before she's exposed and arrested. Resisting all suggestions to defect and save herself, Dominika recklessly immerses herself in the palace intrigues of the Kremlin, searching for the mole's name, and stealing as many of President Putin's secrets for her CIA handlers before her time runs out--even as Putin's dangerous interest in her grows. The treasure trove of her intelligence reporting sends Nate Nash and colleagues on desperate missions to Sevastopol, Istanbul, Khartoum, and Hong Kong. Dominika's report triggers a desperate mole hunt before she's exposed and arrested. Resisting all suggestions to defect and save herself, Dominika recklessly immerses herself in the palace intrigues of the Kremlin, searching for the mole's name, and stealing as many of President Putin's secrets for her CIA handlers before her time runs out--even as Putin's dangerous interest in her grows. The treasure trove of her intelligence reporting sends Nate Nash and colleagues on desperate missions to Sevastopol, Istanbul, Khartoum, and Hong Kong.